The Relationship among Attitudes toward ICT, Collegial Support and TPACK of EFL Teachers - Kurnia Agustin; Aridah Aridah; Weningtyas P. Iswari (Magister Program of English Education, Fakultas Keguruan dan Ilmu Pendidikan Universitas Mulawarman, 2023)
Technological Pedagogical and Content Knowledge (TPACK) promotes real-world context, cultural awareness, a wide range of tools, teamwork and cooperation, and independent learning. It was crucial to understand the connection between TPACK, attitudes toward Information and Communications Technology (ICT), and collegial support. The purpose of this study was to determine teachers' levels of TPACK, attitudes toward ICT, and collegial support. Additionally, this study sought to determine whether attitudes toward ICT and collegial support were significantly related to TPACK. The questionnaire for this study was completed by 49 English as a Foreign Language (EFL) instructors in East Borneo. To examine the data from the survey, t and F tests were run. According to this study, TPACK level and attitudes toward ICT and peer support were significantly correlated. The study showed that the participants had a high category for TPACK level. Secondly, this study found positive results regarding ICT use for teaching and learning. Thirdly, this study showed participants had a high level of collegial support. ICT attitudes and TPACK levels were positively and significantly correlated. Support from peers was positively and significantly correlated with TPACK level. ICT attitudes and peer support were significantly correlated with TPACK level. To raise teachers' TPACK level, educators should have internal teacher development sessions more frequently and encourage teacher associations to share ideas.